(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The purpose of this scientific article is to study the manifestation of linguistic and cultural worldview and to study the linguistic and cultural aspect of learning English through phraseological level units. The study of the conceptual structure allows us to identify deeper and more significant properties of an object or phenomenon. Such properties represent generalized features of an object or phenomenon that are considered the most important and necessary for their identification, since the features of an object or phenomenon form the structure of the concept. The object of this scientific article is phraseological units that express the concepts of the inner world of a person, the specifics of their functioning and interpretation in the English language, and aspects of their use in the process of teaching English.